Damage characterization on human femur bone by means of ultrasonics and acoustic emission. (June 2015) - Strantza, M; Polyzos, D; Louis, O; Boulpaep, F; Van Hemelrijck, D; Aggelis, D G
Abstract: Human bone tissue is characterized as a material with high brittleness. Due to this nature, visible signs of cracking are not easy to be detected before final failure. The main objective of this work is to investigate if the acoustic emission (AE) technique can offer valuable insight to the fracture process of human femur specimens as in other engineering materials characterization. This study describes the AE activity during fracture of whole femur bones under flexural load. Before fracture, broadband AE sensors were used in order to measure parameters like wave velocity dispersion and attenuation. Waveform parameters like the duration, rise time and average frequency, were also examined relatively to the propagation distance as a preparation for the AE monitoring during fracture. After the ultrasonic study, the samples were partly cast in concrete and fixed as cantilevers. A point load was applied on the femur head, which due to the test geometry resulted in a combination of two different patterns of fracture, bending and torsion. Two AE broadband sensors were placed in different points of the sample, one near the fixing end and the other near the femur head. Preliminary analysis shows that parameters like the number of acquired AE signals and their amplitude are well correlated with the load history. Furthermore, the parameters of rise time and frequency can differentiate the two fracture patterns. Additionally, AE allows the detection of the load at the onset of fracture from the micro-cracking events that occur at the early loading stages, allowing monitoring of the whole fracture process. Parameters that have been used extensively for monitoring and characterization of fracture modes of engineering materials seem to poses characterization power in the case of bone tissue monitoring as well.